Vosyliaus Sezemano pažinimo teorija: intuicija, logika ir dialektika. - Jonkus, Dalius (Problems / Problemos, 2020)
Nicolai Hartmann interprets the logic of knowledge as a dialectical process that must reveal the processionality of being itself. Sesemann not only extends Hartmann's philosophical insights, but also supplements them significantly. He also understands the knowledge of reality not as an analysis of static objects, but as a dynamic and temporal reconstruction of becoming reality. Acknowledging the limitations of intuition, he returns to the possibilities of logically formed knowledge. Sesemann argues that the logical constructions of knowledge must maintain a connection with primal intuition. However, logically formed knowledge is limited by its static nature. A dialectic is needed to reveal a dynamically changing being. I will begin the article by discussing the relationship between intuition and logical knowledge, then examine the problem of the ideal being and conclude by evaluating the significance of dialectics in Sesemann's theory of knowledge. According to Sesemann, the dialectic, unlike formal logic, must reveal not the ideal laws of thought, but how live knowledge takes place. Dialectics allows one to analyze being as incomplete and indefinite, as becoming and open to infinite change, it allows one to relate a separate aspect of knowledge to the whole.